HPLC METHOD DEVELOPMENT AND VALIDATION OF RABEPRAZOLE AND LEVOSULPIRIDE IN ITS BULK AND DOSAGE FORM (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Analytical method is heart of pharmaceutical analysis. The present work was attempted to develop accurate, simple and sensitive method for simultaneous estimation of rabeprazole and levosulpiride. The mobile phase was consisted of Buffer: Acetonitrile, with ratio of (70:30) at flow rate was quite satisfactory. In our study, the percentage recovery of LEVO was found to be 99.98%, 100.06%, & 100.1% from 80%, 100%, 120% sample solution respectively. For RABE was found to be 98.99%, 99.46%, & 100.08% from 80%, 100%, 120% sample solution respectively. The obtained percentage recovery of both drugs was found to be within the range. This indicates the proposed method was more accurate than the existing methods. Precision is determined by using the method to assay a sample for a sufficient number of times to obtain statistically valid results. The precision is then expressed as the percentage relative standard deviation. Acceptance criteria for the precision of method is that % RSD should not be more than 2%. In the present study for intermediate precision % RSD for LEVO and RABE was found to be 0.344, 0.242 respectively. % RSD value indicate a good degree of precision within specified range.